ГЕНЕЗИС ПРОБЛЕМ СЕМЬИ И БРАКА И ОТРАЖЕНИЕ ЭТИХ ПРОБЛЕМ В ДУХОВНОМ НАСЛЕДИИ ДЖАДИДОВ (Scientific journal of the Fergana State University, 2026)
This article provides a philosophical analysis of the emergence of family and marriage relationships, and the issue of family in the views of Jadids.